2020
DOI: 10.1111/ctr.14099
|View full text |Cite
|
Sign up to set email alerts
|

Newly diagnosed multiple myeloma patients treated with tandem auto‐allogeneic stem cell transplant have better overall survival with similar outcomes at time of relapse compared to patients who received autologous transplant only

Abstract: Background: Long-term survival in patients progressing after tandem autologousallogeneic stem cell transplant (SCT) has been reported, suggesting a persistent graftvs-myeloma (GvM) effect even after post-transplant progression. Methods: In order to confirm this observation, we updated the results of our previously published cohort of 92 newly diagnosed myeloma patients who received tandem transplant and compared them with 81 contemporary patients who received autologous transplant only. Results: With a median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…In the following years, myeloablation achieved through high-dose chemotherapy and auto-SCT with maximal reduction of MM-cells was separated from allo-SCT with less myelosuppressive but highly immunosuppressive reduced-intensity conditioning (RIC) regimens to prevent treatment-related organ toxicities but allow a sufficient engraftment and GvM effect [ 23 ]. Several prospective trials demonstrated improved OS and PFS after this auto/allo-SCT approach with RIC in the first-line setting as compared to the control arm, mostly tandem auto-SCT, and randomization according to the availability of a human leukocyte antigen (HLA)-identical donor [ 24 , 25 , 26 ] ( Table 1 ). In two studies, prolonged PFS was shown at least in patients with HR cytogenetics [ 4 , 27 , 28 , 29 ] and no study demonstrated inferiority of the auto/allo-SCT arm [ 30 , 31 , 32 , 33 , 34 ], suggesting that HR constellations may be overcome by the allo-SCT.…”
Section: Allogeneic Transplantation In Newly Diagnosed and Relapsed And/or Refractory Myelomamentioning
confidence: 99%
See 2 more Smart Citations
“…In the following years, myeloablation achieved through high-dose chemotherapy and auto-SCT with maximal reduction of MM-cells was separated from allo-SCT with less myelosuppressive but highly immunosuppressive reduced-intensity conditioning (RIC) regimens to prevent treatment-related organ toxicities but allow a sufficient engraftment and GvM effect [ 23 ]. Several prospective trials demonstrated improved OS and PFS after this auto/allo-SCT approach with RIC in the first-line setting as compared to the control arm, mostly tandem auto-SCT, and randomization according to the availability of a human leukocyte antigen (HLA)-identical donor [ 24 , 25 , 26 ] ( Table 1 ). In two studies, prolonged PFS was shown at least in patients with HR cytogenetics [ 4 , 27 , 28 , 29 ] and no study demonstrated inferiority of the auto/allo-SCT arm [ 30 , 31 , 32 , 33 , 34 ], suggesting that HR constellations may be overcome by the allo-SCT.…”
Section: Allogeneic Transplantation In Newly Diagnosed and Relapsed And/or Refractory Myelomamentioning
confidence: 99%
“…However, some trials showing superior PFS but similar OS indicate that the increased TRM may probably counteract the benefit of a reduced relapse rate by allo-SCT [ 29 ]. TRM-rates remained as substantial with 20% at 10 years [ 35 ], but were not worse as compared to the auto-SCT control arm in more than half of the studies [ 24 , 25 , 26 , 28 , 29 , 32 ]. The leading cause of death was organ failure or an infectious complication and in only 6% GvHD [ 17 , 29 ].…”
Section: Allogeneic Transplantation In Newly Diagnosed and Relapsed And/or Refractory Myelomamentioning
confidence: 99%
See 1 more Smart Citation
“…The standard graft-versus-host prophylaxis used in Hovon-50 [62], Italian study [26], BMT CTN [30], and NMAM2000 [28] is cyclosporine in combination with mycophenolate mofetil. In contrast, PETHEMA investigators were using cyclosporine with methotrexate [25] and other groups tacrolimus with mycophenolate mofetil or methotrexate [14,63]. On average, an extensive or moderate-severe chronic GVHD incidence of 40-70% has been reported in these trials.…”
Section: Graft-versus-host Disease Prophylaxismentioning
confidence: 99%